Essential role of germinal vesicle material in the meiotic cell cycle of Xenopus oocytes - Iwashita, Jun (The National Academy of Sciences, 1998)
In almost all animal species, immature oocytes are arrested naturally in the first meiotic prophase, with a large nucleus called the germinal vesicle. A number of previous studies showed that both activation of maturation/M phase-promoting factor (MPF) (assayed by semiquantitative cytological methods) and some other maturational events occur essentially normally in enucleated oocytes from many amphibian species and mice. Hence, for nearly three decades, it has generally been believed that nuclear material is dispensable for MPF activation and the meiotic cell cycle in vertebrate oocytes. Here, we have challenged this view by examining the histone H1 kinase activities and the molecular forms of MPF in experimentally manipulated Xenopus oocytes. We show that oocytes injected with nuclear material undergo much more rapid MPF activation and maturation than uninjected control oocytes. Conversely, enucleated oocytes, unlike nucleated counterparts, undergo only weak MPF activation in meiosis I and no detectable MPF reactivation in meiosis II, the latter accompanying inhibitory tyrosine phosphorylation of cdc2 kinase, the catalytic subunit of MPF. These results argue strongly that nuclear material is indispensable for the meiotic cell cycle, particularly MPF reactivation (or cdc2 tyrosine dephosphorylation) on entry into meiosis II, in Xenopus oocytes. The classical and general view may thus need reconsideration.